Strain Characteristics of Motianling Ductile Shear Zone in Northern Guangxi and its Tectonic Significances - Zhili REN; Ya QIN; Zuohai FENG; Jie WU; Shiyun LIU; Qiaofan HU; Yuming BAI; Pengcheng ZHOU (Kuangchan zonghe liyong)
This is an article in the field of structural geology. In this article, the strain characteristics and tectonic significance of the tile shear zone of Motianling are discussed through macro-microstructure, finite strain measurement of rocks and EBSD structural analysis of quartz. The results show that the Motianling ductile shear zone has typical macro-micro ductile deformation fabrics, including mylonite foliation, rotating porphyry system, S-C fabric, domino structures, asymmetric ocular sphere, quartz dynamic recrystallization, core-mantle structure, mica fish, feldspar mechanical twinning and asymmetric pressure shadow. The finite strain measurement and macro-micro structure shows that the Motianling ductile shear zone extends over 65 km in NNE direction, and its width is 8～12 km. The C-foliation tendency of the mylonite is 220°～356°, the dip angle is 10°～74°, and the extremely dense point occurrence is 285°∠22°. The Motianling ductile shear zone has kinematic characteristics of early sinistral thrust shear and late dextral normal slip shear. The rock strain of Motianling ductile shear zone is mainly flattening strain and tensile strain. At the same time, it shows the shear property of pure shear and simple shear. Quartz EBSD fabric analysis show that the Motianling ductile shear zone is characterized by the late middle-low temperature deformation ( 300～450 ℃ ) superimposed on the early middle-high temperature deformation ( 400～600 ℃ ). The paleo differential stress and strain rate of Motianling ductile shear zone are relatively low, ranging from 10.59～36.31 MPa and 0.63×10-13～87.18×10-13 s-1, respectively. In combination with the above studies and regional geological data, it is considered that the Motianling ductile shear zone was formed in the tectonic setting of recoil after extrusion of the Cathaysia block from SE to the Yangtze block. In the early extrusion and collision stage, the Motianling ductile shear zone has the property of mid-high temperature sinistral thrust shear. After the late orogenic extension, the Motianling ductile shear zone has the property of dextral normal slip shear at mid-low temperature. The above understanding reveals the occurrence, strain characteristics, rheology and dynamics setting of the Motianling ductile shear zone and provides new data for deepening the understand of Caledonian tectonic movement in South China.